Determinants of Customer Patronage of Fast Food Outlets in Benin City - Okolie, Ugo Chucks; Udom, Idongesit David (Universitas Negeri Semarang, 2021)
This study critically examined the factors influencing customer patronage of fast food outlets in Benin City. Specifically, the independent variables examined include quality of service delivery, brand image and price and how they relate to customer patronage. The study adopted survey research design. The population includes all customers that patronize fast food outlets in Benin City, Edo State. Fifty (50) respondents each were chosen in four fast food outlets namely: Mr. Biggs, Mat Ice, Kada Food and Omega Food to have a sample size of two hundred (200) out of which 188 questionnaires were found useable, amounting to 94%. The data analyses were done using both descriptive and inferential statistics. All analyses were done using Statistical Package for Social Sciences (SPSS 22.0) software. The study revealed that there are positive and significant relationship between the independent variables (service quality and brand image) and customer patronage except price that showed negative and not significant relationship with customer patronage. Based on these findings, the study recommended that fast food operators should continue to maintain high quality service delivery that will enhance the brand image of selected fast food outlets.